COVID-19’s Impact on the Transition to Clean Cooking Fuels : Initial Findings from a Case Study in Rural Kenya - Zhang, Yabei; Li, Zijun (World Bank, Washington, DC, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic has magnified household preferences for convenience and affordability, presenting challenges as well as opportunities for the transition to clean cooking fuels. Initial findings from a study in rural Kenya suggest that the pandemic and lockdown have altered household cooking practices and fuel-use patterns. COVID-19 is nudging middle-income households to switch to modern cooking fuels (biogas and electricity), because these have been less disrupted by the COVID restrictions. However, without external support, COVID-19 will push poorer households further down the energy ladder.